Design, evaluation, and future projections of the NARCliM2.0 CORDEX-CMIP6 Australasia regional climate ensemble - G. Di Virgilio; G. Di Virgilio; J. P. Evans; J. P. Evans; F. Ji; F. Ji; E. Tam; J. Kala; J. Andrys; C. Thomas; D. Choudhury; C. Rocha; et al. (Geoscientific Model Development)
NARCliM2.0 (New South Wales and Australian Regional Climate Modelling) comprises two Weather Research and Forecasting (WRF) regional climate models (RCMs) which downscale five Coupled Model Intercomparison Project Phase 6 (CMIP6) global climate models contributing to the Coordinated Regional Downscaling Experiment (CORDEX) over Australasia at 20 km resolution and southeast Australia at 4 km convection-permitting resolution. We first describe NARCliM2.0's design, including selecting two definitive RCMs via testing 78 RCMs using different parameterisations for the planetary boundary layer, microphysics, cumulus, radiation, and land surface model (LSM). We then assess NARCliM2.0's skill in simulating the historical climate versus CMIP3-forced NARCliM1.0 and CMIP5-forced NARCliM1.5 RCMs and compare differences in future climate projections. RCMs using the new Noah multi-parameterisation (Noah-MP) LSM in WRF with default settings confer substantial improvements in simulating temperature variables versus RCMs using Noah Unified. Noah-MP confers smaller improvements in simulating precipitation, except for large improvements over Australia's southeast coast. Activating Noah-MP's dynamic vegetation cover and/or runoff options primarily improves the simulation of minimum temperature. NARCliM2.0 confers large reductions in maximum temperature bias versus NARCliM1.0 and 1.5 (1.x), with small absolute biases of ∼ 0.5 K over many regions versus over ∼ 2 K for NARCliM1.x. NARCliM2.0 reduces wet biases versus NARCliM1.x by as much as 50 % but retains dry biases over Australia's north. NARCliM2.0 is biased warmer for minimum temperature versus NARCliM1.5, which is partly inherited from stronger warm biases in CMIP6 versus CMIP5 GCMs. Under Shared Socioeconomic Pathway (SSP) 3-7.0, NARCliM2.0 projects ∼ 3 K warming by 2060–2079 over inland regions versus ∼ 2.5 K over coastal regions. NARCliM2.0-SSP3-7.0 projects dry futures over most of Australia, except for wet futures over Australia's north and parts of western Australia, which are the largest in summer. NARCliM2.0-SSP1-2.6 projects dry changes over Australia with only few exceptions. NARCliM2.0 is a valuable resource for assessing climate change impacts on societies and natural systems and informing resilience planning by reducing model biases versus earlier NARCliM generations and providing more up-to-date future climate projections utilising CMIP6.